You just need to expand the left side, combine like terms, and solve algebraically. Use the distributive property to expand 5(x + 3) into 5x + 5*3 = 5x + 15. Then you have 5x + 15 = 7x + 3. If you subtract 3 from both sides and then also subtract 5x from both sides, you'll have 12 = 2x. Divide both sides by 2 to get the final answer, x = 6. The procedure is shown step-by-step below.
5x + 15 = 7x + 3
12 = 2x
x = 6
2007-03-18 03:53:13
·
answer #1
·
answered by DavidK93 7
·
0⤊
0⤋
X= 6 this is what u do:
times out the bracket so u get 5x+15
then u get the like terms on each side so u get 15-3 = 7x-5x
then do the calculations so u get 12 = 2x
then to get x by it self to have to take the 2 over the which makes 12 / 2 = x
so x is = 6 :) hope it helps !!!!!!
2007-03-18 10:58:33
·
answer #2
·
answered by Skeenish 1
·
0⤊
0⤋
5(x+3) = 5x + 15. You know how to do that right? Multiply 5 and x, then multiply 5 and 3. Whatever sign is there in the brackets will be the sign you put between the two terms which you get.
5x + 15 = 7x +3
Bring all the terms with x to the left hand side(LHS) and the others to the Right hand side(RHS). When you shift the terms from one side to the other, the sign changes. If it is + it becomes -. If it's on the numerator on one side, it becomes denominator if you shift it to the other and vice versa.
Therefore, 5x-7x = 3 - 15
-2x = -12
There's - sign on both the sides and you can just cancel them out and it becomes +
2x=12
x= 6
2007-03-18 11:16:41
·
answer #3
·
answered by Drools over home made food 6
·
0⤊
0⤋
5(x+3) = 7x + 3
5x + 15 = 7x + 3 :distribute the 5 for (x+3)
15-3 = 7x - 5x : now, combining like terms
12= 2x : divide 12 by 2 to get the value of x.
x= 6 ...........ans.
by checking it out:
5(x+3) = 7x + 3 :substitute the value of x:
5(6 + 3) = 7(6) + 3
30 + 15 = 42 + 3
45 = 45 ...it's correct.
LHS = RHS
2007-03-18 11:05:15
·
answer #4
·
answered by edison c d 4
·
0⤊
0⤋
Ok:
5(x+3)=7x+3 First you do distributive property with the five. And get:
5x+15= 7x+3 Next you want all the X's on one side so you subtract 5x from both sides.
15= 2x+3 Now you subtract 3 from both sides because you want X to be alone.
12= 2x Then you divide each side by 2 so X is alone.
6=x is the answer.
2007-03-18 10:56:39
·
answer #5
·
answered by hereecomesxthesun :] 2
·
0⤊
0⤋
6
2007-03-18 11:27:48
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
It took me like 1 min. to find the answer. Ok, first you have 5(x+3)=7x+3 right?
then you use the distributive property and thats
5x+15=7x+3
after that you combine terms so you do
5x+15=7x+3
-5x -5x
which equals
15=2x+3
then you subtract three from both sides
15=2x+3
-3 -3
and that equals
12=2x
then you divide both sides by 2
12=2x
/2 /2
and x=6!
2007-03-18 11:03:23
·
answer #7
·
answered by raquelita. 1
·
0⤊
0⤋
5x + 15 = 7x + 3
15 - 3 = 7x - 5x
12 = 2x
x = 6
Check:-
5 x 6 + 15 = 45
7 x 6 + 3 = 45
2007-03-18 11:08:05
·
answer #8
·
answered by Como 7
·
0⤊
0⤋
5(x+3)= 7x+3
5*x + 5*3 = 7*x + 3
5x+15= 7x+3
subtract 5x from each side
15=2x+3
subtract 3 from each side
12=2x
divide 2 from each side
6=x
2007-03-18 10:57:49
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
5(x+3)=7x+3
5x+15=7x+3
subtract 5x from both sides to get x's on same side
15=2x+3
subtract 3 from both sides to get full numbers on same side
12=2x
divide out 2 to get x
x=6
check:
5(6)+15=7(6)+3
30+15=42+3
45=45 your answer is correct
Getting the answer is easy but it took forever to write it out for me.
2007-03-18 11:09:16
·
answer #10
·
answered by For_Gondor! 5
·
0⤊
0⤋